Pengembangan Alat Estimasi Pola Peningkatan Kekotoran Panel PV - Wibowo, Sapto; Sigit Setya Wiwaha; Irwan Heryanto/Eryk (Elposys: Jurnal Sistem Kelistrikan, 2023)
Photovoltaic (PV) panels play a pivotal role in converting solar radiation into electrical energy. The efficiency of PV panels is susceptible to the impact of shadows and accumulated dirt on the panel surfaces. This research aims to establish a correlation between the level of dirt accumulation and the resultant power generation. The methodology employed involves a comparative analysis of power output from PV panels under clean and dusty conditions. To quantify the increase in dust over a 3-day data collection period, a glass surface was exposed outdoors to collect dust, serving as a reference for comparison with the PV panel surface. The glass, containing accumulated dust, was then subjected to data retrieval using an LED as a light source. A light intensity sensor (BH1750) was employed to measure the decrease in light intensity as dust coverage increased on the glass surface over time.The results of the PV fouling test, utilizing 10 grams of dust, indicate a relatively stable voltage generation with only a 0.8-volt loss. In contrast, the current generated experienced losses of 0.28 amperes before and after fouling. These losses significantly impact the overall power generation capacity of the PV panel. This research sheds light on the importance of mitigating dust accumulation on PV surfaces to optimize and sustain efficient solar energy conversion.